Korupsi Akademik sebagai Pra-Kondisi Korupsi Struktural: Perspektif Hukum Pidana dalam Pencegahan Tindak Pidana Korupsi - Marwan Parulian Simanjuntak; Via Nurita Dolok Saribu; Yohanes Andis Arya Panca Putra (LPPM Universitas Widya Dharma Pontianak, 2025)
This article analyzes academic corruption as a criminogenic condition that contributes to the emergence of structural corruption from a criminal law perspective. Academic misconduct such as plagiarism, academic bribery, abuse of authority, and manipulation of assessment processes is frequently treated as a mere ethical issue, rather than as a phenomenon with long-term criminal implications. This study employs a normative juridical method using statutory and conceptual approaches. The analysis demonstrates that tolerance toward academic dishonesty functions as an early socialization process that weakens legal compliance and normalizes unlawful behavior. From the standpoint of criminal policy, academic corruption represents a pre-criminal phase that shapes corrupt behavioral patterns before individuals enter public office or bureaucratic structures. Therefore, corruption prevention strategies should incorporate preventive criminal law measures within higher education governance. Strengthening internal legal norms, institutional accountability, and legal awareness in universities is essential to constructing an effective and sustainable anti-corruption framework.